Analisis Paparan Kebisingan Pesawat Terbang di Bandara Babullah Ternate - Zein, Karman; Sagaf, Safrudin (Pascasarjana Universitas Negeri Makassar, 2018)
This study aims to measure exposure to aircraft noise levels in the Babullah Airport area of Ternate. Data collection in this study is observation (observation), which aims to obtain preliminary data relating to the problems studied, besides that data collection also uses noise level measurements carried out at the 0 meter point from the runway to 500 meters at 5 points. The results of the research show that the activities of airplanes at Babullah Ternate Airport began to experience an increase, as indicated by the type of airlines that competed in serving flights at national and domestic levels.Domestic and national flight activities, airplanes at Babullah Ternate Airport greatly affect the environment. The results of this study indicate that the kebanganangan level in the airport area reaches an average of 78.8 db (A) with other environmental parameters such as wind speed and air humidity 12.6 m / s and 81.23%. If the size of the environmental parameters no longer affect noise exposure, the area has noise that exceeds the threshold. To reduce the noise level due to the flight activities at Babullah Ternate Airport, a barrier is needed as well as socializing the danger of noise for humans.